2022
DOI: 10.3389/fmicb.2022.777882
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Salivary and Buccal Mucosal Microbiota by 16S rRNA Sequencing for Forensic Investigations

Abstract: The human microbiome has emerged as a new potential biomarker for forensic investigations with the development of high-throughput sequencing and bioinformatic analysis during the last decade. The oral cavity has many different microbial habitats, with each habit colonized by specific and individualized microbiota. As saliva and buccal mucosa are common biological evidence in forensic science, understanding the differences of microbial communities between the two is important for forensic original identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…The prepared library was measured with a Qubit fluorometer and sequenced after normalization. Sequencing was performed on the MiSeq instrument (Illumina, San Diego, CA, USA) following the paired-end 2 × 300 bp protocol according to the manufacturer’s recommendations [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prepared library was measured with a Qubit fluorometer and sequenced after normalization. Sequencing was performed on the MiSeq instrument (Illumina, San Diego, CA, USA) following the paired-end 2 × 300 bp protocol according to the manufacturer’s recommendations [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The facts that members of these genera can thrive in soil, water, and plants, where human and animal excreta can be also present, and have typically highly dynamic genomes, suggest that these bacteria can serve as vectors of clinically relevant features (e.g. antibiotic resistance, virulence) from the environment to humans (Sanz-García et al 2021 ; Wang et al 2022a , 2022b ). Indeed, the summary provided in Table 1 shows that bacteria of some of these genera hold a broad set of antibiotic resistance genes, generically included in the categories efflux, inactivation, target modification, reduced permeability, among others, that are shared by other Pseudomonadota .…”
Section: The Oral Cavity As Primary or Transient Pseudomona...mentioning
confidence: 99%
“…The broad diversity of oral microbiomes was evidenced by Tierney et al (2019) who, based on the analysis of 1473 oral metagenomes, identified 23 961 508 genes, half of which were unique in each metagenome. Such a uniqueness has led some authors to propose the oral microbiome profile as a valuable tool for biogeography investigations or forensic personal discrimination (Wang et al 2022a(Wang et al , 2022b.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations